PENGARUH CASH HOLDING DAN STRUKTUR KEPEMILIKAN MANAJERIAL TERHADAP INCOME SMOOTHING (Studi Empiris Pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2010 – 2012) - Milka Erika Mambraku; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2014)
This study aimed to examine the effect of variable cash holding and managerial ownership structure of the income smoothing . Income smoothing measured by discretionary accruals , cash holding measured by the ratio of cash and cash equivalents to total assets and managerial ownership structure is measured by the ratio of the number of outstanding shares owned by the management of the total outstanding share capital.This study memnggunakan the data of 63 companies listed on the Indonesian Stock Exchange (IDX) in 2010-2012 . The sampling method used in this study was purposive sampling , is sampling based criteria .The analysis technique used in this study using multiple regression analysis using SPSS 20 . Results of research conducted indicates that the variable cash holding and managerial ownership structure significantly positive effect on income smoothing.